2007
DOI: 10.1115/1.2731412
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Dry-Friction Whirl and Whip Between a Rotor and a Stator

Abstract: This paper addresses recent test results for dry-friction whip and whirl. Authors of these publications suggest that predictions from Black’s 1968 paper (J. Mech. Eng. Sci., 10(1), pp. 1–12) are deficient in predicting their observed transition speeds from whirl to whip and the associated precession frequencies of whirl and whip motion. Predictions from Black’s simple Jeffcott-rotor/point-mass stator are cited. This model is extended here to a multimode rotor and stator model with an arbitrary axial location f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…The lateral interaction between the journal O, and CB inner race O^, will be defined by a Hunt-Crossley nonlinear contact model [12], This approach has been used previously by Bartha [13,14], Wilkes [15] and Wilkes et al, [9], and Childs and Bhattacharya [16], who all obtained As usual, it is good practice to begin with a formal definition of the coordinates used in the analysis. Figure 4 shows the rotor/journal contacting the CB inner race (CBIR), In this case, the displacement of Oj and 0¿,, is…”
Section: Interactions Between the Rotor And Catcher Bearing Inner Racementioning
confidence: 99%
See 1 more Smart Citation
“…The lateral interaction between the journal O, and CB inner race O^, will be defined by a Hunt-Crossley nonlinear contact model [12], This approach has been used previously by Bartha [13,14], Wilkes [15] and Wilkes et al, [9], and Childs and Bhattacharya [16], who all obtained As usual, it is good practice to begin with a formal definition of the coordinates used in the analysis. Figure 4 shows the rotor/journal contacting the CB inner race (CBIR), In this case, the displacement of Oj and 0¿,, is…”
Section: Interactions Between the Rotor And Catcher Bearing Inner Racementioning
confidence: 99%
“…(16) and (17) can be integrated for a range of inner-race speed ratios to determine the lateral forces (Fcai) and torques (Tcai) on the rotor as the inner race speeds up after contact with the thrust bearing occurs. Figure 7 shows the normalized radial and tangential forces and torques versus inner-race speed ratio for the example scenario.…”
Section: (4)mentioning
confidence: 99%
“…Shen et al [21] reported that, under the influence of the initial permanent bow, there are different routes to chaos that could greatly affect the rub-impact. Childs and Bhattacharya [22] presented a new model for predicting the dry frictions whirl and whip between a rotor and a stator. The effect of the centering springs on the bifurcation of a flexible rotor response supported by squeeze film dampers is presented in [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Some papers like e.g. Black [5] and Childs [6] use an identical model only investigating continuous contact (δ = 0) and therefore using the contact condition (4). This simplification gives rise to analytical solutions for continuous contact (see 4.1 and 4.2).…”
Section: Assignment Of the Model To Literaturementioning
confidence: 99%